Said Nursi’s psycho-spiritual therapy for psychological reactions of patients with physical illnesses - Md Rosli, Ahmad Nabil; Md Tahir, Mohd Faiz; Thomas, Nur Sakinah; Gulerce, Hakan (IIUM Press, 2019)
NA